2021
DOI: 10.1002/hep.31776
|View full text |Cite
|
Sign up to set email alerts
|

Male Sex Is Associated With Higher Rates of Liver‐Related Mortality in Primary Biliary Cholangitis and Cirrhosis

Abstract: Background and Aims The impact of sex on the postcirrhosis progression of primary biliary cholangitis (PBC) has not been well defined. Prior studies have suggested that men have worse outcomes but present at more advanced stages of fibrosis than women. This observation, however, has been limited by small numbers of men and even fewer patients with cirrhosis. Approach and Results We investigated the association of sex with the development of all‐cause and liver‐related mortality or transplantation, decompensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 27 publications
5
34
0
Order By: Relevance
“…Interestingly, our results suggested that male gender was an independent risk factor of grade B/C PHLF. This result was similar to the findings noted by John BV and colleagues ( 29 ). The exact mechanisms for the increased prevalence of severe PHLF in men are unclear.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, our results suggested that male gender was an independent risk factor of grade B/C PHLF. This result was similar to the findings noted by John BV and colleagues ( 29 ). The exact mechanisms for the increased prevalence of severe PHLF in men are unclear.…”
Section: Discussionsupporting
confidence: 93%
“…Our study included 273 patients with PBC diagnosed per AASLD criteria, of which 89% were female, which is consistent with prior epidemiologic studies 2,[12][13][14][15] . Out of the 273 patients, 172 underwent abdominal ultrasound, 95 underwent helical CT scan, and 129 underwent MRI/MRCP.…”
Section: Discussionsupporting
confidence: 68%
“…The assembly of this cohort has been described. [ 4 , 5 ] In response to the SARS‐CoV‐2 pandemic, the Veterans Administration (VA) created the national VA COVID‐19 Shared Data Resource using case definitions that were validated across the system and including all veterans with a confirmed laboratory diagnosis of SARS‐CoV‐2 infection, both those tested within the VA and outside the VA. Institutional review boards at all participating VA health systems approved the protocol and waived the need for informed consent.…”
Section: Methodsmentioning
confidence: 99%